Analysis of Factors Affecting Breastfeeding Expenditure on Post Sectio Caesarea Mothers at Sidikalang Regional General Hospital Dairi Regency - Dinar Manalu; Sarma Lumban Raja; Mangatas Silaen (Journal La Medihealtico, 2022)
Breastfeeding provides both short-term and long-term benefits for both the child and the mother, including protecting the child against a variety of acute and chronic disorders. However, the high incidence of CS and the low number of breastfeeding mothers with cesarean delivery have a lot of negative effects on the breastfeeding process. Data obtained from Dairi district in 2021 showed that the coverage of breastfeeding was only 40%, while in Sidikalang Hospital, post-sc mothers gave breast milk. only 35%. The purpose of this study was to determine the effect of factors that influence the release of breast milk for post SC mothers at Sidikalang Hospital, Dairi Regency in 2021. This type of research was mixed method with sequential explanatory design. The population is 120 respondents and purposive sampling is 54 respondents. 3 key informants representing Post SC mothers , 8 supporting informants. Data analysis used univariate, bivariate and multivariate analysis as well as qualitative data analysis including reduction, display and conclusion drawing/verification. The results showed that there was an effect of breastfeeding frequency (sig 0.000), breast care (sig 0.002), mother's diet (sig 0.000) breastfeeding technique. (sig 0.000) the SPEOS method (sig 0.000 ) , while there was no effect of hospitalization (sig 0.210), birth weight (sig 0.201), gestational age (sig 0.201), the most influential variables were maternal food with a value of B = 4.084 and OR = 59.93 for the expenditure of breast milk for post SC mothers at Sidikalang Hospital, Dairi Regency in 2021.